Biodegradable resin composition

JP2023110156A5Inactive Publication Date: 2025-01-07MITSUBISHI CHEM CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022011405
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-01-28
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Conventional biodegradable resins face issues with varying biodegradation rates and mechanical properties, leading to potential loss of performance and environmental risks from additives like bactericides and antibacterial agents.

Method used

Incorporating a specific amount of borate hydrate, particularly sodium tetraborate hydrate, into biodegradable resins to adjust biodegradation rates without significantly altering mechanical properties, using borate hydrates that are naturally occurring and environmentally benign.

Benefits of technology

The biodegradable resin composition effectively delays biodegradation while maintaining mechanical properties, ensuring complete biodegradation and minimizing environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide a biodegradable resin composition that has a biodegradation rate controlled for delayed biodegradation without a significant change in physical properties.SOLUTION: A biodegradable resin composition comprises 1.0-5.3 pts.mass of borate hydrate relative to 100 pts.mass of a biodegradable resin.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a biodegradable resin composition. [Background technology]

[0002] In recent years, concerns about ecosystem and environmental pollution caused by marine disposal of plastic products have become apparent. Various regulations are being enacted around the world, with a view to preventing environmental pollution. For example, Europe is currently enacting regulations and laws banning the use of disposable plastic shopping bags and disposable plastic containers such as cups and plates in retail. To be exempt from the use bans imposed by this law, products must be made from biomass with a minimum biomass content specified and be compostable in ordinary households (home compostable products). Recently, there has also been a demand for marine biodegradable plastic products, which decompose in the ocean if plastic products are discharged into the ocean.

[0003] Conventionally, biodegradable plastics (biodegradable resins) include aliphatic polyesters such as polybutylene terephthalate / adipate (hereinafter abbreviated as PBAT), polylactic acid (hereinafter abbreviated as PLA), polybutylene succinate (hereinafter abbreviated as PBS) and polybutylene succinate / adipate (hereinafter abbreviated as PBSA), and polyhydroxyalkanoates (hereinafter abbreviated as PHA). Further PHAs include poly(3-hydroxybutyrate) (hereinafter abbreviated as PHB), poly(3-hydroxybutyrate / 3-hydroxyvalerate) (hereinafter abbreviated as PHBV), poly(3-hydroxybutyrate / 3-hydroxyhexanoate) (hereinafter abbreviated as PHBH), and poly(3-hydroxybutyrate / 4-hydroxybutyrate).

[0004] These resins not only differ in the rate and rate of biodegradation of the resins themselves, but also in mechanical properties such as tensile elongation at break and flexural modulus. Therefore, they are generally used in combination with other resins or mixed with other secondary materials and additives depending on the application and location of use.

[0005] Biodegradable resin products are completely biodegradable in nature and in composting equipment, but at the same time, they must maintain their functionality (e.g., mechanical strength) while in use. Therefore, there is a demand for technology that can control the biodegradation rate depending on the location, period, and purpose of use. In particular, in agricultural, fishery, civil engineering materials, etc. used outdoors, the environments of use are diverse, and in these applications, depending on the environment of use, the biodegradation of biodegradable resins may proceed too quickly, preventing the intended purpose of the use from being fully achieved. Therefore, there has been a need for a technology that can slow down the biodegradation rate compared to that of conventional biodegradable resins.

[0006] Patent Document 1 discloses a biodegradable agricultural plastic sheet in which the entire sheet is made of biodegradable plastic, and the biodegradation rate at both widthwise ends of the sheet is slower than at the center of the sheet, while Patent Document 2 discloses an agricultural film in which portions with a slow biodegradation rate are formed by methods such as molding the sheet to be thicker in some areas, applying non-biodegradable resin or a resin with a slow biodegradation rate to some areas, bonding, fusing, two-color molding, or co-extrusion molding non-biodegradable resin or a resin with a slow biodegradation rate to some areas, or applying or adding a bactericide or antifungal agent to some areas. Furthermore, Patent Document 3 discloses a biodegradable resin composition containing an aliphatic polyester, starch, and an aliphatic aromatic polyester, and the decomposition rate of which is controlled. A biodegradable resin composition is disclosed in which the rate of biodegradation is adjusted by containing an organic antibacterial agent. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 9-107808 [Patent Document 2] Japanese Patent Application Laid-Open No. 2001-17008 [Patent Document 3] Japanese Patent Application Laid-Open No. 2008-13602 [Patent Document 4] Japanese Patent Application Publication No. 5-117507 Summary of the Invention [Problem to be solved by the invention]

[0008] Conventional technologies (Patent Documents 1 and 2) that thicken a molded body in certain areas can maintain the required strength for a certain period of time, but these technologies change physical properties such as flexibility compared to a molded body of the original thickness, and the weight also increases, raising concerns that the original performance may not be maintained or that costs may increase.

[0009] As in Patent Document 3, by using a technique of combining a resin with slow biodegradability, it is possible to delay biodegradation compared to the original biodegradable resin, but there is a risk that the mechanical properties may vary significantly because a resin with different physical properties such as flexibility is combined. Furthermore, as in Patent Document 4, the technology of compounding a bactericide or antibacterial agent can adjust the biodegradation rate without significantly changing the physical properties. However, these bactericides and antibacterial agents release compounds that do not naturally occur in nature and heavy metals into the environment. Therefore, even after the biodegradable resin has biodegraded, only these compounds remain in the soil, which may have a negative impact on the ecosystem.

[0010] The present invention has been made in view of the above background, and aims to provide a biodegradable resin composition and a molded article thereof that are ultimately completely biodegradable without significantly changing the physical properties of the biodegradable resin itself, such as mechanical properties and flexibility, and that have a biodegradable resin composition whose biodegradation rate is adjusted so that biodegradation is delayed. [Means for solving the problem]

[0011] As a result of extensive research to solve the above problems, the inventors discovered that by blending a specific amount of borate hydrate with a biodegradable resin, the biodegradation rate can be adjusted so that biodegradation is delayed, leading to the present invention.

[0012] That is, the gist of the present invention lies in the following [1] to [5]. [1] A biodegradable resin composition comprising 1.0 to 5.3 parts by mass of borate hydrate per 100 parts by mass of a biodegradable resin. [2] The biodegradable resin composition according to [1], wherein the borate hydrate is sodium tetraborate hydrate. [3] The biodegradable resin composition according to [2], wherein the hydration number of the sodium tetraborate hydrate is 5 to 10. Here, the hydration number is the value of n when the composition formula of sodium tetraborate hydrate is expressed in the form of Na2B4O7·nH2O. [4] The biodegradable resin composition according to any one of [1] to [3], wherein the biodegradable resin is an aliphatic polyester resin. [5] The biodegradable resin composition according to [4], wherein the aliphatic polyester resin is a polyester containing, as main components, a structural unit derived from an aliphatic diol and a structural unit derived from an aliphatic dicarboxylic acid. [Effects of the Invention]

[0013] According to the present invention, there is provided a biodegradable resin composition whose biodegradation rate can be adjusted so as to delay biodegradation without significantly changing the physical properties of the biodegradable resin itself, and which ultimately biodegrades. [Brief explanation of the drawings]

[0014] [Figure 1] 1 is a graph showing the relationship between the number of days elapsed and the weight retention rate in a biodegradability test for Example 1 of the present invention and Comparative Examples 1 and 2. DETAILED DESCRIPTION OF THE INVENTION

[0015] Hereinafter, an embodiment of the present invention will be described in detail. The present invention is not limited to the following description, and can be implemented by any modification within the scope of the gist of the present invention. In this specification, when "~" is used to express a numerical value or a physical property value, the value before and after the "~" is used to include the values ​​before and after the "~"

[0016] [Borate hydrate] The biodegradable resin composition of the present invention is characterized by containing a certain amount of borate hydrate relative to the biodegradable resin.

[0017] Boric acid and its salts are naturally found widely in soil, oceans, and other parts of the natural world (see, for example, "Environmental Health Criteria No. 204 Boron"). Borates are also essential trace elements for plants, and are designated as "boron-based fertilizers" in the official standards for fertilizers established by the Ministry of Agriculture, Forestry and Fisheries. Therefore, even if small amounts of borate components are released into the environment from the biodegradable resin composition of the present invention, it is believed that the adverse impact on the environment will be extremely small.

[0018] The anions that make up borates undergo dehydration condensation to form various polyborate ions, such as triborate ions, tetraborate ions, and pentaborate ions. These polyborates and salts of boric acid are generally collectively called borates. Boric acid and salts of polyboric acid are hydrolyzed in water to form tetrahydroxyborate ions [B(OH)4 -

[0033] and boric acid [B(OH)]. Therefore, the borate hydrate contained in the biodegradable resin composition of the present invention is not particularly limited as long as it is essentially a salt consisting of borate ions or polyborate ions.

[0019] Examples of cations constituting borates include sodium ions, potassium ions, lithium ions, magnesium ions, calcium ions, ammonium ions, etc. Among these, sodium salts are preferred because they are inexpensive, have low environmental toxicity, and are easily soluble in water.

[0020] As the sodium borate, sodium tetraborate hydrate is preferred, with sodium tetraborate decahydrate [Na2B4O7·10H2O] (borax) being the most preferred.

[0021] The borate salt contained in the biodegradable resin composition of the present invention is characterized by having water of hydration. When melt-kneaded with a biodegradable resin, the borate salt containing water of hydration releases water of crystallization, causing the crystal grains to disintegrate. Furthermore, the water acts as a solvent and plasticizer, allowing the borate salt to be uniformly finely dispersed in the biodegradable resin composition. Therefore, when molded into a film or fiber, molded articles with good mechanical properties, appearance, and feel can be obtained. For example, when the composition formula of sodium tetraborate is expressed as Na2B4O7·nH2O, if the hydration number n is 10 (decahydrate), it will release water of crystallization and melt at 62°C or higher, and if n is in the range of 5 to 10, it will release water of crystallization at temperatures below 200°C. On the other hand, when n = 0 (anhydrous), the melting point is 742°C, and the crystal grains will retain their original shape even after melt-kneading, resulting in a good molded product. Therefore, the value of n is preferably 5 to 10.

[0022] The amount of borate hydrate contained in the biodegradable resin composition of the present invention is 1.0 to 5.3 parts by mass per 100 parts by mass of biodegradable resin. If the amount of borate hydrate is 1.0 part by mass or more, a biodegradation retarding effect can be obtained. On the other hand, if the amount exceeds 5.3 parts by mass, foaming due to released moisture and a decrease in molecular weight due to hydrolysis during kneading and molding may occur, making it difficult to obtain a molded product with good physical properties and appearance. By adjusting the amount within this range, the biodegradation rate of the molded product can be adjusted depending on the purpose and location of use.

[0023] [Biodegradable resin] The biodegradable resin contained in the biodegradable resin composition is a plastic having biodegradability, and any of those conventionally known as biodegradable plastics can be used. The biodegradable resin may be a polyester containing, as main constituent components, constituent units derived from a diol and constituent units derived from a dicarboxylic acid, or may be an aliphatic oxycarboxylic acid resin (C). The term "main constituent unit" generally refers to a constituent unit that is contained in the polyester resin in an amount of 80% by mass or more, and may be contained in an amount of 90% by mass or more. It may also be 100% by mass if no constituent units other than the main constituent unit are contained.

[0024] The polyester containing a diol-derived structural unit and a dicarboxylic acid-derived structural unit as main structural components is not particularly limited, and examples thereof include an aliphatic polyester resin (A) and an aliphatic-aromatic polyester resin (B). Two or more of the aliphatic polyester resin (A) and the aliphatic-aromatic polyester resin (B) may be mixed and used.

[0025] Each biodegradable resin will be explained below. The aliphatic polyester resin (A) and the aliphatic-aromatic polyester resin (B) are polymers each having a repeating unit, and each repeating unit is also called a compound unit corresponding to the compound from which the repeating unit is derived. For example, a repeating unit derived from an aliphatic diol is also called an "aliphatic diol unit," a repeating unit derived from an aliphatic dicarboxylic acid is also called an "aliphatic dicarboxylic acid unit," and a repeating unit derived from an aromatic dicarboxylic acid is also called an "aromatic dicarboxylic acid unit."

[0026] <Aliphatic polyester resin (A)> The aliphatic polyester resin (A) is preferably an aliphatic polyester resin containing an aliphatic diol unit and an aliphatic dicarboxylic acid unit as main constituent units.

[0027] The aliphatic polyester resin (A) preferably contains succinic acid units, and more preferably contains succinic acid units in a proportion of 5 mol% to 100 mol% of all dicarboxylic acid units. The aliphatic polyester resin (A) may be a mixture of aliphatic polyester resins containing different amounts of succinic acid units. For example, an aliphatic polyester resin containing no aliphatic dicarboxylic acid units other than succinic acid (containing only succinic acid units as aliphatic dicarboxylic acid units) may be blended with an aliphatic polyester resin containing aliphatic dicarboxylic acid units other than succinic acid, and the amount of succinic acid units in the aliphatic polyester resin (A) may be adjusted to fall within the above-mentioned preferred range.

[0028] More specifically, the aliphatic polyester resin (A) is a polyester resin containing an aliphatic diol unit represented by the following formula (1) and an aliphatic dicarboxylic acid unit represented by the following formula (2). -OR 1 -O- (1) -OC-R 2 -CO- (2)

[0029] In formula (1), R 1 represents a divalent aliphatic hydrocarbon group. 2 represents a divalent aliphatic hydrocarbon group. The aliphatic diol unit and the aliphatic dicarboxylic acid unit represented by the above formula (1) and (2) may be derived from a compound derived from petroleum or a compound derived from plant raw materials, but are preferably derived from a compound derived from plant raw materials.

[0030] When the aliphatic polyester resin (A) is a copolymer, the aliphatic polyester resin (A) may contain two or more aliphatic diol units represented by formula (1), and the aliphatic polyester resin (A) may contain two or more aliphatic dicarboxylic acid units represented by formula (2).

[0031] As mentioned above, the aliphatic dicarboxylic acid units represented by formula (2) preferably contain succinic acid units in an amount of 5 mol % to 100 mol % based on the total dicarboxylic acid units. By setting the amount of succinic acid constituent units in the aliphatic polyester resin (A) within the above-mentioned range, it is possible to obtain a biodegradable resin composition that has improved moldability and excellent heat resistance and decomposability. For the same reason, the amount of succinic acid units in the aliphatic polyester resin (A) is preferably 10 mol % or more, more preferably 50 mol % or more, even more preferably 64 mol % or more, and particularly preferably 68 mol % or more based on the total dicarboxylic acid units. Hereinafter, the ratio of succinic acid units to all dicarboxylic acid units in the aliphatic polyester resin (A) may be referred to as the "succinic acid unit amount."

[0032] Furthermore, the aliphatic dicarboxylic acid units represented by formula (2) preferably contain one or more types of aliphatic dicarboxylic acid units other than succinic acid in an amount of 5 mol % to 50 mol % based on the total dicarboxylic acid units. By copolymerizing aliphatic dicarboxylic acid units other than succinic acid within the above-mentioned range, the crystallinity of the aliphatic polyester resin (A) can be reduced, and the biodegradation rate can be increased. For the same reason, the amount of aliphatic dicarboxylic acid units other than succinic acid in the aliphatic polyester resin (A) is preferably 10 mol % to 45 mol %, more preferably 15 mol % to 40 mol %, based on the total dicarboxylic acid units.

[0033] The aliphatic diol that provides the diol unit represented by formula (1) is not particularly limited, but from the viewpoint of moldability and mechanical strength, an aliphatic diol having 2 to 10 carbon atoms is preferred, and an aliphatic diol having 4 to 6 carbon atoms is particularly preferred. Examples include ethylene glycol, 1,3-propanediol, 1,4-butanediol, and 1,4-cyclohexanedimethanol, with 1,4-butanediol being particularly preferred. Two or more of the above aliphatic diols can also be used.

[0034] The aliphatic dicarboxylic acid component that provides the aliphatic dicarboxylic acid unit represented by formula (2) is not particularly limited, but is preferably an aliphatic dicarboxylic acid having 2 to 40 carbon atoms or a derivative thereof such as an alkyl ester, and particularly preferably an aliphatic dicarboxylic acid having 4 to 10 carbon atoms or a derivative thereof such as an alkyl ester. Examples of aliphatic dicarboxylic acids having 2 to 40 carbon atoms other than succinic acid or derivatives thereof such as an alkyl ester include adipic acid, suberic acid, sebacic acid, dodecanedioic acid, dimer acid, etc., and derivatives thereof such as alkyl esters. Among these, adipic acid and sebacic acid are preferred, and adipic acid is particularly preferred. Note that two or more types of the aliphatic dicarboxylic acid components can be used, and in this case, a combination of succinic acid and adipic acid is preferred.

[0035] The aliphatic polyester resin (A) contains a repeating unit ( The aliphatic oxycarboxylic acid may have an aliphatic oxycarboxylic acid unit). Specific examples of the aliphatic oxycarboxylic acid component that provides the aliphatic oxycarboxylic acid unit include lactic acid, glycolic acid, 2-hydroxy-n-butyric acid, 2-hydroxycaproic acid, 6-hydroxycaproic acid, 2-hydroxy-3,3-dimethylbutyric acid, 2-hydroxy-3-methylbutyric acid, 2-hydroxyisocaproic acid, 6-hydroxycaproic acid, and the like, as well as derivatives thereof, such as lower alkyl esters or intramolecular esters. When optical isomers exist in these, they may be in any of the D-form, L-form, or racemic form, and may be in any of the forms of solid, liquid, and aqueous solution. Among these, lactic acid, glycolic acid, or derivatives thereof are particularly preferred. These aliphatic oxycarboxylic acids may be used alone or in a mixture of two or more.

[0036] When the aliphatic polyester resin (A) contains these aliphatic oxycarboxylic acid units, from the viewpoint of moldability, the content thereof is preferably 20 mol % or less, more preferably 10 mol % or less, even more preferably 5 mol % or less, and most preferably 0 mol % (not included), based on 100 mol % of all structural units constituting the aliphatic polyester resin (A).

[0037] The aliphatic polyester resin (A) may have an increased melt viscosity by copolymerizing a trifunctional or higher aliphatic polyhydric alcohol, a trifunctional or higher aliphatic polycarboxylic acid or its acid anhydride, or a trifunctional or higher aliphatic polyoxycarboxylic acid component.

[0038] Specific examples of trifunctional aliphatic polyhydric alcohols include trimethylolpropane, glycerin, etc., and specific examples of tetrafunctional aliphatic polyhydric alcohols include pentaerythritol, etc. These may be used alone or in combination of two or more. A specific example of a trifunctional aliphatic polycarboxylic acid or its acid anhydride is propanetricarboxylic acid or its acid anhydride, and a specific example of a tetrafunctional polycarboxylic acid or its acid anhydride is cyclopentanetetracarboxylic acid or its acid anhydride, etc. These may be used alone or in combination of two or more.

[0039] Trifunctional aliphatic oxycarboxylic acids are divided into (i) types having two carboxyl groups and one hydroxyl group in the same molecule, and (ii) types having one carboxyl group and two hydroxyl groups. Either type can be used, but from the viewpoints of moldability, mechanical strength, and the appearance of molded products, types having two carboxyl groups and one hydroxyl group in the same molecule, such as malic acid, are preferred. More specifically, malic acid is preferred. Tetrafunctional aliphatic oxycarboxylic acid components are divided into (i) types having three carboxyl groups and one hydroxyl group in the same molecule, (ii) types having two carboxyl groups and two hydroxyl groups in the same molecule, and (iii) types having three hydroxyl groups and one carboxyl group in the same molecule. Either type can be used, but those having multiple carboxyl groups are preferred. More specifically, examples include citric acid and tartaric acid. These can be used alone or in combination.

[0040] When the aliphatic polyester resin (A) contains such structural units derived from trifunctional or higher functional components, the content thereof, with all structural units constituting the aliphatic polyester resin (A) being 100 mol %, is generally 0 mol % or more in lower limit, preferably 0.01 mol % or more in upper limit, and generally 5 mol % or less, preferably 2.5 mol % or less in upper limit.

[0041] The aliphatic polyester resin (A) can be produced by a known method for producing polyesters. The polycondensation reaction can be carried out under any suitable conditions that have been conventionally used, and is not particularly limited. Usually, the degree of polymerization is further increased by carrying out a reduced pressure operation after the esterification reaction has proceeded.

[0042] When a diol component forming a diol unit and a dicarboxylic acid component forming a dicarboxylic acid unit are reacted during the production of the aliphatic polyester resin (A), the amounts of the diol component and the dicarboxylic acid component used are set so that the aliphatic polyester resin (A) produced has the desired composition. Usually, the diol component and the dicarboxylic acid component react in substantially equimolar amounts, but the diol component is usually used in a 1 to 20 mol % excess over the dicarboxylic acid component because it is distilled off during the esterification reaction.

[0043] When the aliphatic polyester resin (A) contains components (optional components) other than the essential components such as aliphatic hydroxycarboxylic acid units and polyfunctional component units, the corresponding compounds (monomers and oligomers) are reacted so that the aliphatic hydroxycarboxylic acid units and polyfunctional component units have the desired compositions. In this case, there are no limitations on the timing or method of introducing the optional components into the reaction system, and they are optional as long as the aliphatic polyester resin (A) can be produced.

[0044] For example, the timing and method of introducing the aliphatic hydroxycarboxylic acid into the reaction system are not particularly limited as long as it is before the polycondensation reaction between the diol component and the dicarboxylic acid component. Examples include (1) a method in which the catalyst is dissolved in an aliphatic hydroxycarboxylic acid solution in advance and mixed, and (2) a method in which the catalyst is introduced into the reaction system and mixed at the same time when the raw materials are charged.

[0045] The timing of introducing the compound that forms the polyfunctional component unit may be such that it is charged simultaneously with other monomers or oligomers at the initial stage of polymerization, or it may be charged after the transesterification reaction and before the start of decompression. However, charging it simultaneously with other monomers or oligomers is preferred from the viewpoint of simplifying the process.

[0046] The aliphatic polyester resin (A) is usually produced in the presence of a catalyst. Any catalyst that can be used in the production of known polyester resins can be selected as the catalyst as long as it does not significantly impair the effects of the present invention. Examples of suitable catalysts include metal compounds such as germanium, titanium, zirconium, hafnium, antimony, tin, magnesium, calcium, and zinc. Among these, germanium compounds and titanium compounds are preferred.

[0047] Examples of germanium compounds that can be used as catalysts include organic germanium compounds such as tetraalkoxygermanium, and inorganic germanium compounds such as germanium oxide and germanium chloride. Among these, germanium oxide, tetraethoxygermanium, and tetrabutoxygermanium are preferred in terms of cost and availability, with germanium oxide being particularly preferred.

[0048] Examples of titanium compounds that can be used as catalysts include organic titanium compounds such as tetraalkoxytitanium compounds such as tetrapropyl titanate, tetrabutyl titanate, and tetraphenyl titanate. Among these, tetrapropyl titanate, tetrabutyl titanate, and the like are preferred in terms of price and availability.

[0049] In addition, other catalysts may be used in combination as long as the object of the present invention is not impaired. The catalysts may be used alone or in any combination and ratio of two or more.

[0050] The amount of catalyst used is arbitrary as long as it does not significantly impair the effects of the present invention, but is usually 0.0005% by mass or more, more preferably 0.001% by mass or more, and usually 3% by mass or less, preferably 1.5% by mass or less, based on the amount of monomer used. If the amount is below the lower limit of this range, the effect of the catalyst may not be exhibited, while if the amount is above the upper limit, the production cost may increase, the resulting polymer may be significantly discolored, or the hydrolysis resistance may decrease.

[0051] The timing of introducing the catalyst is not particularly limited as long as it is before the polycondensation reaction, and it may be introduced when the raw materials are charged or when pressure reduction is started. When an aliphatic oxycarboxylic acid unit is introduced, it is preferably introduced simultaneously with a monomer or oligomer that forms an aliphatic oxycarboxylic acid unit, such as lactic acid or glycolic acid, when the raw materials are charged, or by dissolving the catalyst in an aqueous aliphatic oxycarboxylic acid solution and introducing it. In particular, the method of dissolving the catalyst in an aqueous aliphatic oxycarboxylic acid solution and introducing it is preferred because it increases the polymerization rate.

[0052] The reaction conditions, such as temperature, polymerization time, and pressure, used in producing the aliphatic polyester resin (A) may be any as long as they do not significantly impair the effects of the present invention. The reaction temperature for the esterification reaction and / or transesterification reaction between the dicarboxylic acid component and the diol component is typically 150°C or higher, preferably 180°C or higher, and typically 260°C or lower, preferably 250°C or lower. The reaction atmosphere is typically an inert atmosphere such as nitrogen or argon. The reaction pressure is typically normal pressure to 10 kPa, with normal pressure being preferred. The reaction time is typically 1 hour or higher, and typically 10 hours or shorter, preferably 6 hours or shorter, and more preferably 4 hours or shorter. If the reaction temperature is too high, excessive unsaturated bonds may be generated, resulting in gelation caused by the unsaturated bonds, making it difficult to control the polymerization.

[0053] The pressure for the polycondensation reaction after the esterification reaction and / or transesterification reaction between the dicarboxylic acid component and the diol component is usually 0.01 × 10 3 Pa or more, preferably 0.03 x 10 3 Pa or higher, with an upper limit of 1.4×10 3 Pa or less, preferably 0.4×10 3 It is desirable to carry out the reaction under a vacuum of 100 Pa or less. The lower limit of the reaction temperature is usually 150°C or higher, preferably 180°C or higher, and the upper limit is usually 260°C or lower, preferably 250°C or lower. The lower limit of the reaction time is usually 2 hours or higher, and the upper limit is usually 15 hours or lower, preferably 10 hours or lower. If the reaction temperature is too high, excessive generation of unsaturated bonds may cause gelation due to the unsaturated bonds, making it difficult to control the polymerization.

[0054] When producing the aliphatic polyester resin (A), a chain extender such as a carbonate compound or a diisocyanate compound can also be used. In this case, the amount of the chain extender is usually 10 mol% or less, preferably 5 mol% or less, and more preferably 3 mol% or less, as the proportion of carbonate bonds or urethane bonds in the aliphatic polyester resin (A) when all structural units constituting the aliphatic polyester resin are 100 mol%. However, the presence of urethane bonds or carbonate bonds in the aliphatic polyester resin (A) may inhibit biodegradability. Therefore, the carbonate bonds should be less than 1 mol%, preferably 0.5 mol% or less, more preferably 0.1 mol% or less, and the urethane bonds should be 0.55 mol% or less, preferably 0.3 mol% or less, more preferably 0.12 mol% or less, and even more preferably 0.05 mol% or less, relative to all structural units constituting the aliphatic polyester resin (A). This amount, calculated per 100 parts by mass of the aliphatic polyester resin (A), is 0.9 parts by mass or less, preferably 0.5 parts by mass or less, more preferably 0.2 parts by mass or less, and even more preferably 0.1 parts by mass or less. In particular, if the amount of urethane bonds exceeds the upper limit, decomposition of the urethane bonds may cause problems in the film-forming process, such as smoke and odor from the molten film exiting the die outlet, and film breakage due to foaming may occur in the molten film, making it impossible to stably mold it. The carbonate bond amount and urethane bond amount in the aliphatic polyester resin (A) are 1 H-NMR and 13 It can be calculated from the results of NMR measurements such as C-NMR.

[0055] Specific examples of the carbonate compound as the chain extender include diphenyl carbonate, ditolyl carbonate, bis(chlorophenyl) carbonate, m-cresyl carbonate, dinaphthyl carbonate, dimethyl carbonate, diethyl carbonate, dibutyl carbonate, ethylene carbonate, diamyl carbonate, dicyclohexyl carbonate, In addition, carbonate compounds derived from hydroxy compounds such as phenols and alcohols, or carbonate compounds of the same or different types of hydroxy compounds, can also be used.

[0056] Specific examples of the diisocyanate compound include known diisocyanates such as 2,4-tolylene diisocyanate, a mixture of 2,4-tolylene diisocyanate and 2,6-tolylene diisocyanate, 1,5-naphthylene diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, tetramethylxylylene diisocyanate, 2,4,6-triisopropylphenyl diisocyanate, 4,4'-diphenylmethane diisocyanate, and tolidine diisocyanate.

[0057] Other chain extenders such as dioxazoline and silicate esters may also be used. Specific examples of silicate esters include tetramethoxysilane, dimethoxydiphenylsilane, dimethoxydimethylsilane, and diphenyldihydroxysilane.

[0058] High molecular weight polyester resins using these chain extenders (coupling agents) can also be produced using conventional techniques. After polycondensation is complete, the chain extender is added to the reaction system in a homogeneous molten state without a solvent, and reacted with the polyester obtained by polycondensation.

[0059] More specifically, a polyester with substantially hydroxyl terminal groups and a weight-average molecular weight (Mw) of 20,000 or more, preferably 40,000 or more, obtained by catalytically reacting a diol component with a dicarboxylic acid component, can be reacted with the above-mentioned chain extender to obtain a higher molecular weight polyester resin. Prepolymers with a weight-average molecular weight of 20,000 or more can be produced with the use of a small amount of chain extender without gel formation during the reaction, even under harsh conditions such as in a molten state, because they are not affected by residual catalyst. Here, the weight-average molecular weight (Mw) of the polyester resin is determined by gel permeation chromatography (GPC) using chloroform as the solvent at 40°C, converted into a monodisperse polystyrene value.

[0060] Therefore, when further increasing the molecular weight of a polyester resin using, for example, the above-mentioned diisocyanate compound as a chain extender, it is preferable to use a prepolymer having a weight-average molecular weight of 20,000 or more, preferably 40,000 or more. If the weight-average molecular weight is less than 20,000, the amount of diisocyanate compound used to increase the molecular weight may increase, resulting in a decrease in heat resistance. Using such a prepolymer, a polyester resin having urethane bonds with a linear structure linked via urethane bonds derived from the diisocyanate compound is produced.

[0061] The pressure during chain extension is usually 0.01 MPa or more and 1 MPa or less, preferably 0.05 MPa or more and 0.5 MPa or less, more preferably 0.07 MPa or more and 0.3 MPa or less, and most preferably normal pressure.

[0062] The lower limit of the reaction temperature during chain extension is usually 100° C. or higher, preferably 150° C. or higher, more preferably 190° C. or higher, and most preferably 200° C. or higher, and the upper limit is usually 250° C. or lower, preferably 240° C. or lower, and more preferably 230° C. or lower. If the reaction temperature is too low, the viscosity will be high, making it difficult to achieve a uniform reaction, and high stirring power will tend to be required. If the reaction temperature is too high, gelation or decomposition of the polyester resin will tend to occur concomitantly.

[0063] The lower limit of the time for chain extension is usually 0.1 minute or more, preferably 1 minute or more, and more preferably 5 minutes or more, and the upper limit is usually 5 hours or less, preferably 1 hour or less, more preferably 30 minutes or less, and most preferably 15 minutes or less. If the time for chain extension is too short, the effect of adding the chain extender tends not to be exerted, and if it is too long, gelation or decomposition of the polyester resin tends to occur concomitantly.

[0064] The molecular weight of the aliphatic polyester resin (A) can be measured by gel permeation chromatography (GPC). The weight average molecular weight (Mw) of the aliphatic polyester resin (A) using monodisperse polystyrene as the standard is usually 10,000 or more and 1,000,000 or less, but is preferably 20,000 or more and 500,000 or less, and more preferably 50,000 or more and 400,000 or less, because this is advantageous in terms of moldability and mechanical strength.

[0065] The melt flow rate (MFR) of the aliphatic polyester resin (A) is measured at 190°C under a load of 2.16 kg according to JIS K7210 (1999), and is usually 0.1 g / 10 min or more and 100 g / 10 min or less, but from the viewpoint of moldability and mechanical strength, it is preferably 50 g / 10 min or less, particularly preferably 40 g / 10 min or less. The MFR of the aliphatic polyester resin (A) can be adjusted by the molecular weight.

[0066] The melting point of the aliphatic polyester resin (A) is preferably 70° C. or higher, more preferably 75° C. or higher, and is preferably 170° C. or lower, more preferably 150° C. or lower, and particularly preferably lower than 130° C. When there are multiple melting points, it is preferable that at least one of the melting points is within the above range. The elastic modulus of the aliphatic polyester resin (A) is preferably 180 to 1000 MPa. If the melting point is outside the above range, moldability will be poor, if the modulus of elasticity is less than 180 MPa, problems will likely occur in moldability, and if the modulus of elasticity exceeds 1000 MPa, impact strength will tend to deteriorate.

[0067] The method for adjusting the melting point and elastic modulus of the aliphatic polyester resin (A) is not particularly limited. For example, the melting point and elastic modulus can be adjusted by selecting the type of copolymerization component of the aliphatic dicarboxylic acid component other than succinic acid, adjusting the copolymerization ratio of each component, or combining these.

[0068] The aliphatic polyester resin (A) is not limited to one type, and two or more types of aliphatic polyester resins (A) differing in the types and ratios of constituent units, production methods, physical properties, etc. may be blended and used.

[0069] <Aliphatic-aromatic polyester resin (B)> Examples of the aliphatic-aromatic polyester resin (B) include those in which at least a portion of the repeating units of the above-mentioned aliphatic polyester resin (A) have been replaced with aromatic compound units, preferably polyester resins containing aliphatic diol units, aliphatic dicarboxylic acid units, and aromatic dicarboxylic acid units as main constituent units, in which a portion of the aliphatic dicarboxylic acid units of the above-mentioned aliphatic polyester resin (A) have been replaced with aromatic dicarboxylic acid units.

[0070] Examples of the aromatic compound unit include an aromatic diol unit having an aromatic hydrocarbon group which may have a substituent, an aromatic dicarboxylic acid unit having an aromatic hydrocarbon group which may have a substituent, an aromatic dicarboxylic acid unit having an aromatic heterocyclic group which may have a substituent, and an aromatic oxycarboxylic acid unit having an aromatic hydrocarbon group which may have a substituent. The aromatic hydrocarbon group and aromatic heterocyclic group may be a single ring, or may be one in which multiple rings are bonded or condensed together. Specific examples of the aromatic hydrocarbon group include 1,2-fluoro-2-(2-methyl-2-propanol)-1,2-diol, ... Examples of the aromatic heterocyclic group include a 2,5-furandiyl group, a 1,3-phenylene group, a 1,4-phenylene group, a dinaphthylene group, a diphenylene group, etc. Specific examples of the aromatic heterocyclic group include a 2,5-furandiyl group, etc.

[0071] Specific examples of aromatic dicarboxylic acid components that provide aromatic dicarboxylic acid units include terephthalic acid, isophthalic acid, naphthalenedicarboxylic acid, diphenyldicarboxylic acid, 2,5-furandicarboxylic acid, etc. Among these, terephthalic acid is preferred.

[0072] The aromatic dicarboxylic acid component may be a derivative of an aromatic dicarboxylic acid compound. For example, derivatives of the aromatic dicarboxylic acid components exemplified above are preferred, and among these, lower alkyl esters having 1 to 4 carbon atoms and acid anhydrides are mentioned. Specific examples of derivatives of aromatic dicarboxylic acid compounds include lower alkyl esters such as methyl esters, ethyl esters, propyl esters, and butyl esters of the aromatic dicarboxylic acid components exemplified above; and cyclic acid anhydrides of the aromatic dicarboxylic acid components exemplified above, such as succinic anhydride. Among these, dimethyl terephthalate is preferred.

[0073] Specific examples of aromatic diol components that provide aromatic diol units include xylylene glycol, 4,4'-dihydroxybiphenyl, 2,2-bis(4'-hydroxyphenyl)propane, 2,2-bis(4'-β-hydroxyethoxyphenyl)propane, bis(4-hydroxyphenyl)sulfone, and bis(4-β-hydroxyethoxyphenyl)sulfonic acid. The aromatic diol component may be a derivative of an aromatic diol compound. Alternatively, the aromatic diol component may be a compound having a structure in which a plurality of aliphatic diol compounds and / or aromatic diol compounds are dehydrated and condensed with each other.

[0074] Specific examples of aromatic oxycarboxylic acid components that provide aromatic oxycarboxylic acid units include p-hydroxybenzoic acid and p-β-hydroxyethoxybenzoic acid. The aromatic oxycarboxylic acid component may be a derivative of an aromatic oxycarboxylic acid compound. Alternatively, it may be a compound (oligomer) having a structure in which a plurality of aliphatic oxycarboxylic acid compounds and / or aromatic oxycarboxylic acid compounds are dehydrated and condensed with each other. That is, an oligomer may be used as a raw material.

[0075] When the aromatic compound component that provides these aromatic compound units has optical isomers, any of the D-isomer, L-isomer, and racemic isomer may be used. Furthermore, the aromatic compound component is not limited to the above examples, as long as it can provide an aromatic compound unit. Furthermore, the aromatic compound component may be used alone, or two or more kinds may be used in any combination and ratio.

[0076] The aliphatic-aromatic polyester resin (B) preferably uses an aromatic dicarboxylic acid component as the component that provides the aromatic compound unit. In this case, the content of the aromatic dicarboxylic acid unit is preferably 10 mol% to 80 mol% based on the total amount of the aliphatic dicarboxylic acid unit and the aromatic dicarboxylic acid unit (100 mol%). Furthermore, it is preferable to use terephthalic acid or 2,5-furandicarboxylic acid as the aromatic dicarboxylic acid component. In this case, the aliphatic-aromatic polyester resin (B) is preferably a polybutylene terephthalate adipate and / or polybutylene terephthalate succinate resin. Furthermore, polybutylene-2,5-furandicarboxylate resin is also preferred as the aliphatic-aromatic polyester resin (B).

[0077] The aliphatic-aromatic polyester resin (B) can be produced in the same manner as the aliphatic polyester resin (A) described above, using at least an aromatic compound component as a raw material.

[0078] The molecular weight of the aliphatic-aromatic polyester resin (B) can be measured by gel permeation chromatography (GPC). The weight average molecular weight (Mw) of the aliphatic-aromatic polyester resin (B) using monodisperse polystyrene as the standard is usually 10,000 or more and 1,000,000 or less, but is preferably 30,000 or more and 800,000 or less, and more preferably 50,000 or more and 600,000 or less, because this is advantageous in terms of moldability and mechanical strength.

[0079] The melt flow rate (MFR) of the aliphatic-aromatic polyester resin (B) is The MFR is measured at 190°C under a load of 2.16 kg according to K7210 (1999), and is usually 0.1 g / 10 min or more and 100 g / 10 min or less, but from the viewpoint of moldability and mechanical strength, it is preferably 50 g / 10 min or less, and particularly preferably 30 g / 10 min or less. The MFR of the aliphatic-aromatic polyester resin (B) can be adjusted by the molecular weight.

[0080] The melting point of the aliphatic-aromatic polyester resin (B) is usually 60° C. or higher, preferably 70° C. or higher, more preferably 80° C. or higher, and is preferably 150° C. or lower, more preferably 140° C. or lower, and particularly preferably 120° C. or lower. When there are multiple melting points, it is preferable that at least one of the melting points is within the above range. The elastic modulus of the aliphatic-aromatic polyester resin (B) is preferably 180 to 1000 MPa. If the melting point is outside the above range, moldability will be poor, if the modulus of elasticity is less than 180 MPa, problems will likely occur in moldability, and if the modulus of elasticity exceeds 1000 MPa, impact strength will tend to deteriorate.

[0081] The method for adjusting the melting point and elastic modulus of the aliphatic-aromatic polyester resin (B) is not particularly limited, but it is possible to adjust them, for example, by selecting the type of copolymerization component of the aliphatic dicarboxylic acid component other than the aromatic dicarboxylic acid component, adjusting the copolymerization ratio of each, or combining them.

[0082] The aliphatic-aromatic polyester resin (B) is not limited to one type, and two or more types of aliphatic-aromatic polyester resins (B) differing in the type and ratio of constituent units, production method, physical properties, etc. can be blended and used.

[0083] <Aliphatic hydroxycarboxylic acid resin (C)> The aliphatic oxycarboxylic acid resin (C) has an aliphatic oxycarboxylic acid unit as a main constituent unit, and the aliphatic oxycarboxylic acid unit is preferably represented by the following formula (3). -OR 3 -CO- (3) (In the above formula (3), R 3 represents a divalent aliphatic hydrocarbon group or a divalent alicyclic hydrocarbon group.

[0084] Specific examples of the aliphatic oxycarboxylic acid component that provides the aliphatic oxycarboxylic acid unit of formula (3) include lactic acid, glycolic acid, 2-hydroxy-n-butyric acid, 2-hydroxycaproic acid, 2-hydroxy-3,3-dimethylbutyric acid, 2-hydroxy-3-methylbutyric acid, 2-hydroxyisocaproic acid, 6-hydroxycaproic acid, and mixtures thereof. When optical isomers exist in these, either the D- or L-isomer may be used. Among these, lactic acid or 6-hydroxycaproic acid is preferred. Two or more of these aliphatic oxycarboxylic acid components may also be used in combination.

[0085] Furthermore, a urethane bond, an amide bond, a carbonate bond, an ether bond, etc. can be introduced into the aliphatic oxycarboxylic acid resin (C) to the extent that it does not affect biodegradability.

[0086] The method for producing the aliphatic hydroxycarboxylic acid resin (C) is not particularly limited, and it can be produced by a known method such as direct polymerization of hydroxycarboxylic acid or ring-opening polymerization of a cyclic compound.

[0087] The molecular weight of the aliphatic oxycarboxylic acid resin (C) can be measured by gel permeation chromatography (GPC). The weight average molecular weight (Mw) of the aliphatic oxycarboxylic acid resin (C) using monodisperse polystyrene as the standard is usually 10,000 or more and 1,000,000 or less, but is preferably 20,000 or more and 500,000 or less, and more preferably 50,000 or more and 400,000 or less, because this is advantageous in terms of moldability and mechanical strength.

[0088] The melt flow rate (MFR) of the aliphatic hydroxycarboxylic acid resin (C) is measured at 190°C under a load of 2.16 kg according to JIS K7210 (1999), and is usually 0.1 g / 10 min or more and 100 g / 10 min or less, but from the viewpoint of moldability and mechanical strength, it is preferably 50 g / 10 min or less, particularly preferably 40 g / 10 min or less. The MFR of the aliphatic hydroxycarboxylic acid resin (C) can be adjusted by the molecular weight.

[0089] The melting point of the aliphatic oxycarboxylic acid resin (C) is preferably 50° C. or higher, more preferably 55° C. or higher, and is preferably 200° C. or lower, more preferably 190° C. or lower, and particularly preferably lower than 180° C. When there are multiple melting points, it is preferable that at least one of the melting points is within the above range. The elastic modulus of the aliphatic oxycarboxylic acid resin (C) is preferably 180 to 4000 MPa. If the melting point is outside the above range, moldability will be poor, if the modulus of elasticity is less than 180 MPa, problems will likely occur in moldability, and if the modulus of elasticity exceeds 4000 MPa, impact strength will tend to deteriorate.

[0090] The method for adjusting the melting point and elastic modulus of the aliphatic hydroxycarboxylic acid resin (C) is not particularly limited. For example, the melting point and elastic modulus can be adjusted by selecting the type of copolymerization component other than the aliphatic hydroxycarboxylic acid, adjusting the copolymerization ratio of each component, or combining these components.

[0091] As the aliphatic oxycarboxylic acid resin (C), polyhydroxyalkanoates (D) described below can also be preferably used. Polyhydroxyalkanoate (hereinafter sometimes referred to as PHA) (D) is an aliphatic polyester containing a repeating unit represented by the general formula: [-CHR-CH2-CO-O-] (wherein R is an alkyl group having 1 to 15 carbon atoms), and is a copolymer containing 3-hydroxybutyrate units as the main structural unit.

[0092] From the viewpoints of moldability and thermal stability, the polyhydroxyalkanoate (D) preferably contains 80 mol% or more, and more preferably 85 mol% or more, of 3-hydroxybutyrate units as a constituent component. Furthermore, polyhydroxyalkanoates (D) produced by microorganisms are preferred. Specific examples of polyhydroxyalkanoates (D) include poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) copolymer resins and poly(3-hydroxybutyrate-co-3-hydroxyvalerate-co-3-hydroxyhexanoate) copolymer resins. In particular, poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) copolymer resin, ie, PHBH, is preferred from the viewpoint of molding processability and the physical properties of the resulting molded article.

[0093] In polyhydroxyalkanoate (D), 3-hydroxybutyrate (hereinafter sometimes referred to as 3HB) and copolymerized 3-hydroxyhexanoate (hereinafter sometimes referred to as 3 From the viewpoints of molding processability and molded article quality, the constituent ratio of the copolymer resin with a comonomer such as 3-hydroxybutyrate (sometimes referred to as HH), i.e., the monomer ratio in the copolymer resin, is preferably 3-hydroxybutyrate / comonomer = 97 / 3 to 80 / 20 (mol % / mol %), and more preferably 95 / 5 to 85 / 15 (mol % / mol %). If this comonomer ratio is less than 3 mol %, molding may be difficult because the molding temperature and the thermal decomposition temperature are close to each other. If the comonomer ratio exceeds 20 mol %, crystallization of the polyhydroxyalkanoate (D) may be slow, which may reduce productivity.

[0094] The ratio of each monomer in the polyhydroxyalkanoate (D) can be measured by gas chromatography as follows. Approximately 20 mg of dried PHA is added to 2 ml of a sulfuric acid / methanol mixture (15 / 85 by mass) and 2 ml of chloroform, sealed, and heated at 100°C for 140 minutes to obtain the methyl ester of the PHA decomposition product. After cooling, 1.5 g of sodium bicarbonate is added little by little to neutralize the mixture, and the mixture is left to stand until the evolution of carbon dioxide gas stops. 4 ml of diisopropyl ether is added and mixed well, and the monomer unit composition of the PHA decomposition product in the supernatant is analyzed by capillary gas chromatography to determine the ratio of each monomer in the copolymer resin.

[0095] The weight average molecular weight (hereinafter sometimes referred to as Mw) of the polyhydroxyalkanoate (D) can be measured by the above-mentioned gel permeation chromatography (GPC). The weight average molecular weight (Mw) using monodisperse polystyrene as the standard substance is usually 200,000 or more and 2,500,000 or less, but is preferably 250,000 or more and 2,000,000 or less, more preferably 300,000 or more and 1,000,000 or less, because this is advantageous in terms of moldability and mechanical strength. A weight average molecular weight of less than 200,000 If the molecular weight is more than 2,500,000, the mechanical properties may be poor, and if the molecular weight is more than 2,500,000, molding processing may become difficult.

[0096] The melt flow rate (MFR) of the polyhydroxyalkanoate (D), as measured at 190°C under a load of 2.16 kg according to JIS K7210 (1999), is preferably 1 g / 10 min or more and 100 g / 10 min or less, but from the viewpoints of moldability and mechanical strength, is more preferably 80 g / 10 min or less, and particularly preferably 50 g / 10 min or less. The MFR of the polyhydroxyalkanoate (D) can be adjusted by the molecular weight.

[0097] The melting point of the polyhydroxyalkanoate (D) is preferably 100° C. or higher, more preferably 120° C. or higher, and is preferably 180° C. or lower, more preferably 170° C. or lower, and particularly preferably lower than 160° C. When there are multiple melting points, it is preferable that at least one of the melting points is within the above range.

[0098] Polyhydroxyalkanoate (D) can be produced by, for example, a microorganism such as Alcaligenes eutrophus AC32 strain, which is obtained by introducing a PHA synthase gene derived from Aeromonas caviae into Alcaligenes eutrophus (international deposit under the Budapest Treaty, international depository authority: National Institute of Advanced Industrial Science and Technology International Patent Organism Depositary (6-1 Central, 1-1 Higashi, Tsukuba, Ibaraki Prefecture, Japan), original deposit date: August 12, 1996, transferred on August 7, 1997, deposit number FERM BP-6038 (transferred from original deposit FERM P-15786)) (J. Bacteriol., 179, 4821 (1997)).

[0099] As the polyhydroxyalkanoate (D), commercially available products can be used. An example of a commercially available polyhydroxyalkanoate (D) containing 3-hydroxybutyrate units and 3-hydroxyhexanoate units as main constituent units is "PHBH X331" manufactured by Kaneka Corporation. N", "PHBH X131A", "PHBH X151A", etc. can be used.

[0100] In this embodiment, the aliphatic oxycarboxylic acid resin (C), including the polyhydroxyalkanoate (D), is not limited to one type, and two or more types of aliphatic oxycarboxylic acid resins (C) differing in the type of constituent units, the ratio of constituent units, the production method, the physical properties, etc., can be blended and used.

[0101] <Other ingredients> In addition to the borate hydrate described above, the biodegradable resin composition may contain, as "other components," one or more of various additives such as fillers, plasticizers, antistatic agents, antioxidants, light stabilizers, ultraviolet absorbers, dyes, pigments, hydrolysis inhibitors, crystal nucleating agents, antiblocking agents, weathering agents, heat stabilizers, flame retardants, release agents, antifogging agents, surface wetting improvers, incineration aids, dispersing aids, various surfactants, and slip agents. The biodegradable resin composition may also contain functional additives such as a freshness-preserving agent and an antibacterial agent.

[0102] These other components can be blended as desired within the range that does not impair the effects of the present invention, and one type may be used alone, or two or more types may be used in combination.

[0103] In order not to impair the physical properties of the biodegradable resin composition, the content of these other components in the biodegradable resin composition is usually preferably such that the total amount of the other components is 0.01% by mass or more and 40% by mass or less relative to the total amount of the biodegradable resin composition of the present invention.

[0104] <Method for producing biodegradable resin composition> The biodegradable resin composition is produced by kneading the biodegradable resin and the borate hydrate in a kneader to disperse the borate hydrate in the biodegradable resin. Other resins and other components may also be mixed in the kneader, if necessary, together with the borate hydrate and the biodegradable resin.

[0105] This mixing step is carried out by mixing the borate hydrate and biodegradable resin, and other resins and other components used as needed, in a predetermined ratio simultaneously or in any order using a mixer such as a tumbler, V-type blender, Nauta mixer, Banbury mixer, kneading roll, or extruder, and preferably further melt-kneading the mixture.

[0106] The kneader used in the mixing step may be a melt kneader. The extruder may be either a twin-screw extruder or a single-screw extruder, with a twin-screw extruder being more preferred.

[0107] The temperature during melt-kneading is preferably 140 to 220°C. This temperature range makes it possible to shorten the time required for the melting reaction, prevent resin deterioration, and further improve practical physical properties such as impact resistance and moist heat resistance. From the same perspective, the melt-kneading temperature is more preferably 150 to 210°C.

[0108] As for the melt-kneading time, from the viewpoint of more reliably avoiding resin deterioration, etc., it is necessary to avoid an unnecessarily long time, and it is preferably from 20 seconds to 20 minutes, more preferably from 30 seconds to 15 minutes. Therefore, it is preferable to set the melt-kneading temperature and time conditions so as to satisfy these melt-kneading conditions.

[0109] The borate hydrate is preferably powdered before mixing with the biodegradable resin, which allows the borate hydrate to be uniformly dispersed in the biodegradable resin composition, resulting in a molded article that is biodegradable as well as having excellent mechanical properties and appearance.

[0110] Methods for obtaining powdered borate hydrate include, for example, pulverization using a mill, cutter mill, jet mill, crush mill, or other grinding machine. The particle size of the powdered borate hydrate is usually 2 mm or less, preferably 1.7 mm or less, and more preferably 1.5 mm or less, from the viewpoint of easy uniform mixing with the biodegradable resin in a short time. The particle size of the borate hydrate can be measured by various known methods, such as sieving.

[0111] Since the hydration number of borate hydrate may change due to efflorescence or moisture absorption, it is preferable to store it in a sealed container until just before melt-kneading. The hydration number can be appropriately adjusted by methods such as recrystallization from an aqueous solution, exposure to moist air or dry air, or drying at a predetermined temperature. The hydration number can be measured as follows. For example, sodium tetraborate hydrate becomes anhydrous when heated above 350°C, and the weight loss when dried to constant weight at this temperature is considered to be the amount of water of hydration contained. The original hydration number can be calculated by converting this amount of water of hydration into a molar ratio.

[0112] [Molded body] The biodegradable resin composition can be molded by various molding methods applicable to general-purpose plastics. Examples of such molding methods include compression molding (compression molding, laminate molding, stampable molding), injection molding, extrusion molding, coextrusion molding (film molding by inflation molding or T-die method, laminate molding, pipe molding, wire / cable molding, molding of profiled materials), heat press molding, blow molding (various blow moldings), calendar molding, solid molding (uniaxial stretch molding, biaxial stretch molding, roll molding, stretch-oriented nonwoven fabric molding, thermoforming (vacuum forming, pressure forming), plastic processing, powder molding (rotational molding), and various nonwoven fabric moldings (dry method, adhesive method, entanglement method, spunbonding method, etc.). Among these, injection molding, extrusion molding, compression molding, or heat press molding, especially extrusion molding or injection molding, is preferred. Specific shapes of sheets, films, and fibers are preferred.

[0113] Furthermore, a biodegradable resin molded article obtained by molding a biodegradable resin composition can be subjected to various secondary processing steps in order to impart surface functions such as chemical functions, electrical functions, magnetic functions, mechanical functions, friction / wear / lubrication functions, optical functions, thermal functions, biocompatibility, etc. Examples of secondary processing steps include embossing, painting, bonding, printing, metallizing (plating, etc.), machining, and surface treatments (antistatic treatment, corona discharge treatment, plasma treatment, photochromism treatment, physical vapor deposition, chemical vapor deposition, coating, etc.).

[0114] [Application] Biodegradable resin molded articles are particularly suitable for use in agricultural and forestry materials, fishing materials, civil engineering materials, etc., which are used outdoors, underground, underwater, or in wet environments. Specific examples include extrusion-molded articles (for example, film products such as agricultural mulch films, mushroom cultivation films, and tree protection films, sheet products such as water-retaining sheets, and textile products such as fishing lines, fishing nets, aquaculture nets, vegetation nets, and ropes), injection-molded articles (stakes, seedling pots, and mushroom bed cultivation containers), etc. They are also suitable for use in compost bags and garbage bags, which are expected to be stored for a certain period of time at home, in a business, or elsewhere. [Example]

[0115] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to the following examples as long as it does not deviate from the gist of the invention. The values ​​of various production conditions and evaluation results in the following examples represent preferred upper or lower limit values ​​in the embodiments of the present invention, and preferred ranges may be defined by a combination of the above-mentioned upper or lower limit values ​​and the values ​​in the following examples or values ​​between the examples.

[0116] [Biodegradable resin] The following aliphatic polyester resin (A) was used as the biodegradable resin. Aliphatic polyester resin (A): Polybutylene succinate adipate (PBSA) BioPBS FD92PM manufactured by PTTMCCBiochem

[0117] [Hydrated and anhydrous borate salts] The following borate materials were used: Sodium tetraborate decahydrate: "Borax" manufactured by USBorax. Formula: Na2B4O7·10H2O Sodium tetraborate pentahydrate: "Neobor" manufactured by USBorax. Formula: Na2B4O7·5H2O Sodium tetraborate anhydrous: "Dehybor" manufactured by USBorax, formula: Na2B4O7

[0118] [Examples 1 to 3, Comparative Examples 1 to 6] The biodegradable resin and borate (hydrate or anhydrous) were blended in the proportions shown in Table 1, and the mixture was mixed in a small twin-screw mixer (DSM Xplore Micro 15cc Twin Screw Using a "Compounder," melt-kneading was carried out in a nitrogen atmosphere at 170°C for 4 minutes. Thereafter, the resulting resin composition was taken out as a molten strand and allowed to cool. The kneading state at this time was evaluated as follows, and the results are shown in Table 1.

[0119] <Evaluation of kneading properties> The appearance of the strand when taken out was evaluated according to the following criteria. Good: Mixing was possible without any problems. Poor: Significant foaming. If the evaluation is good, it is possible to stably produce a bubble-free resin composition suitable for molding.

[0120] The strand-like resin composition obtained above was chopped into pellets and subjected to the following evaluations. The results are shown in Table 1. <Intrinsic viscosity evaluation> The intrinsic viscosity (IV) (dL / g) of the resin composition was determined using an Ubbelohde viscometer as follows: A resin composition sample was dissolved at 110°C in a mixed solvent of phenol / 1,1,2,2-tetrachloroethane (1 / 1 by mass) to prepare a solution with a concentration of 0.5 g / dL. The number of seconds it took for the sample solution and the solvent alone to fall at 30°C was measured, and the intrinsic viscosity (IV) (dL / g) was calculated using the following formula: IV=((1+4K H η sp ) 0.5 -1) / (2K H C) where η sp =η / η0-1, where η is the time it takes for the sample solution to fall, η0 is the time it takes for the solvent alone to fall, C is the concentration of the sample solution (g / dL), and K H is Huggins' constant. K H was set to 0.33. In the aliphatic polyester resin (A) used in this example, if the IV is 1.5 or more, a molded article with little decrease in molecular weight and excellent mechanical strength can be obtained.

[0121] The pellets obtained above were molded into a sheet having a thickness of approximately 120 μm using a heat press molding machine set at 170° C. The dispersion state of the borate in the obtained sheet was evaluated as follows, and the results are shown in Table 1. <Dispersibility evaluation> The sheet was observed under transmitted light and evaluated according to the following criteria. Good: Translucent, with barely visible borate particles. Poor: Grained borate is clearly visible. If the evaluation is good, the molded article obtained has a good appearance, a good feel, and good mechanical strength.

[0122] The biodegradability of the sheet obtained above was evaluated as follows, and the results are shown in Figure 1. <Biodegradability test> The resin composition molded into a sheet was cut into 50 mm x 30 mm rectangles, which were then buried in a polyethylene Tupperware container containing a 1:1 mixture of gardening soil ("Flower and Vegetable Culture Soil" manufactured by Iris Ohyama Co., Ltd.) with a moisture content of 20% RH and compost (Yawata Bussan Co., Ltd., inoculant for biodegradation tests) by mass, the container was closed, and the container was left to stand in a thermostatic chamber at 28°C. Each test piece was periodically removed and the weight change was measured, and the weight retention rate (the ratio of the weight after a specified number of days to the weight before the test) was calculated.

[0123] [Table 1]

[0124] Table 1 shows that when the hydration number of the borate hydrate is in the range of 5 to 10 and the content of the borate hydrate is 5.3 parts by mass or less per 100 parts by mass of the biodegradable resin, a composition with good kneadability, little decrease in strength, and good dispersibility can be obtained.

[0125] From FIG. 1, it can be seen that the effect of delaying biodegradation can be obtained if the content of borate hydrate is 1.0 part by mass or more relative to 100 parts by mass of biodegradable resin.

Claims

1. A biodegradable resin composition comprising 1.0 to 5.3 parts by mass of a borate hydrate per 100 parts by mass of a biodegradable resin.

2. The biodegradable resin composition according to claim 1 , wherein the borate hydrate is sodium tetraborate hydrate.

3. The biodegradable resin composition according to claim 2, wherein the hydration number of the sodium tetraborate hydrate is 5 to 10. However, the hydration number is determined by dividing the composition formula of sodium tetraborate hydrate by Na 2 B 4 O 7 ・nH 2 This is the value of n when expressed in the form of O.

4. The biodegradable resin composition according to any one of claims 1 to 3, wherein the biodegradable resin is a polyester containing, as main components, a structural unit derived from a diol and a structural unit derived from a dicarboxylic acid.

5. The biodegradable resin composition described in claim 4, wherein the diol is an aliphatic diol and the dicarboxylic acid is an aliphatic dicarboxylic acid.

6. A biodegradable resin composition described in any one of claims 1 to 3, wherein the biodegradable resin is a polyester containing an aliphatic oxycarboxylic acid unit as a main constituent unit.